Past Imperfect? Reflections on the Evolution of Canadian Federal Government Records Appraisal - Bailey, Catherine A. (Archivaria, 2013)
Well-documented appraisal decisions, based on established archival theory and practice, and appropriately taken within a legal and policy framework, are essential in a government context, as archivists are increasingly held directly accountable by society for their recommendations to preserve or destroy records. An examination of Canadian federal records disposition and appraisal methodology and its documentation shows a long-term evolutionary progression through several different eras. Experience gained through the practice of appraisal within the most recent era, combined with research into the development of Canadian federal records disposition practices over the past 140 years (including evidence from the archival holdings and operational records of Library and Archives Canada) demonstrates that there are fundamental principles and key concepts that can and should support appraisal documentation. Such documentation, it is argued, should also be based on four core components – context, description, analysis, and decision – regardless of the specific methodology, process, or approach that an archives might use. It is argued that these principles, concepts, and components, rooted in history and actual practices, should be the foundation for the documentation necessary to account for appraisal decisions. RÉSUMÉ Des décisions d’évaluation qui sont bien documentées, qui sont fondées sur la théorie et la pratique archivistiques bien établies et qui sont prises dans un cadre légal et politique approprié sont essentielles dans un contexte gouvernemental, et la société tient les archivistes de plus en plus imputables de leurs décisions de conserver ou de détruire des documents d’archives. Une analyse de la méthodologie de disposition et d’évaluation des documents d’archives du gouvernement canadien et des documents connexes révèle une progression à longue échelle, au fil de plusieurs époques différentes. L’expérience acquise en effectuant l’évaluation au cours de l’époque la plus récente, de pair avec une recherche au sujet du développement des pratiques de disposition des documents d’archives du gouvernement canadien pendant les 140 dernières années (y compris des preuves trouvées dans les documents d’archives et les documents opérationnels de Bibliothèque et Archives Canada), montrent qu’il existe des principes fondamentaux et des concepts clés qui peuvent et qui devraient appuyer la documentation liée à l’évaluation. On avance qu’une telle documentation devrait aussi s’appuyer sur quatre composantes de base – le contexte, la description, l’analyse et la décision – peu importe la méthodologie spécifique, le processus ou l’approche qu’un centre d’archives peut choisir d’adopter. On soutient que ces principes, concepts et composantes, bien enracinés dans l’histoire et les pratiques actuelles, devraient servir de fondement à la documentation nécessaire pour rendre compte des décisions d’évaluation.